A Cryogenic Test Rig for Dynamically Operated Plate‐Fin Heat Exchangers. Issue 8 (17th May 2021) - Fritsch, Philipp; Hoffmann, Rainer; Flüggen, Rainer; Haider, Patrick; Rehfeldt, Sebastian; Klein, Harald
Abstract: Flexible operation of air separation units may lead to enhanced thermal stress on the main heat exchanger, typically an aluminum plate‐fin heat exchanger. Hence, a large, cryogenic test rig has been built to investigate fatigue effects of dynamic operation. Nitrogen streams at –175 °C and 50 °C are applied to induce a highly repetitive series of temperature changes in two plate‐fin heat exchangers, which are extensively equipped with measurement technology to collect 3D temperature and strain data and to detect the provoked fatigue damages. Results of the measurements will be used to improve computational lifetime estimation tools. Abstract : Flexible operation of air separation units may lead to enhanced thermal stress on the main heat exchanger. Hence, a large cryogenic test rig has been built to investigate fatigue effects of dynamic operation in aluminum plate‐fin heat exchangers. Extensive measurement technology is applied to determine the dynamic 3D state and detect the provoked fatigue damages.